Dreaming the Graphic Novel: The Novelization of Comics - Williams, Paul (Rutgers University Press, 2020)
Winner of the Best Book Award in Comics History from the Grand Comics Database Honorable Mention, 2019-2020 Research Society for American Periodicals Book PrizeThe term "graphic novel" was first coined in 1964, but it wouldn't be broadly used until the 1980s, when graphic novels such as Watchmen and Maus achieved commercial success and critical acclaim. What happened in the intervening years, after the graphic novel was conceptualized yet before it was widely recognized? Dreaming the Graphic Novel examines how notions of the graphic novel began to coalesce in the 1970s, a time of great change for American comics, with declining sales of mainstream periodicals, the arrival of specialty comics stores, and (at least initially) a thriving underground comix scene. Surveying the eclectic array of long comics narratives that emerged from this fertile period, Paul Williams investigates many texts that have fallen out of graphic novel history. As he demonstrates, the question of what makes a text a 'graphic novel' was the subject of fierce debate among fans, creators, and publishers, inspiring arguments about the literariness of comics that are still taking place among scholars today. Unearthing a treasure trove of fanzines, adverts, and unpublished letters, Dreaming the Graphic Novel gives readers an exciting inside look at a pivotal moment in the art form's development.